Penerapan Gimkit Sebagai Media Pembelajaran pada Mata Pelajaran Bahasa Inggris untuk Meningkatkan Minat Belajar Siswa Kelas VII di SMP Negeri 2 Kadugede - Fahrezi, Rifki; Gustiana, Eva (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve student learning outcomes using Gimkit as a learning medium. The research method used is quantitative with a type of Quasi Experiment using a research design known as Nonequivalent Control Group Design, conducted at SMP Negeri 2 Kadugede. The population used in this study is students in class VII A and VII D, totaling 54 students. Data collection techniques involved observation, interview techniques, and questionnaires. The data analysis techniques used are normality test, homogeneity test, hypothesis test, or T-test. The results showed that the average learning interest of students in the class using Gimkit was 41.12, which was higher than that of the class without Gimkit, which was 30.04. This 10.08 point difference was statistically significant (p = 0.000), indicating that the use of Gimkit is effective in increasing students’ learning interest in English at SMP Negeri 2 Kadugede. Based on the results of the Paired Samples T-Test, the significance value obtained was 0.000 (< 0.05), thus H₀ is rejected and H₁ is accepted. This means that there is a significant difference in learning interest between students who used Gimkit and those who did not. Therefore, the use of Gimkit as a learning medium has been proven to enhance students’ interest in learning English.